DAMPAK KEBIJAKAN KUALITAS SUMBER DAYA MANUSIA PEGAWAI NEGERI SIPIL DILINGUNGAN PEMERINTAH KECAMATAN SIAU TIMUR KABUPATEN KEPULAUAN SITARO (Suatu Studi Di Kantor Kecamatan Siau Timur) - Masambe, Stein; Kiyai, Burhanuddin; Plangiten, Novva (Sam Ratulangi University, 2016)
ABSTRACT: This study is based on the results of the initial observation that the performance of employeesgovernment environments Eastern District of Siau indicated relatively low. This condition is presumablyrelated to the implementation of policies not optimal development of human resources quality civil servantsin the region. Thus, this study aims to: (1) Examine the impact of the quality of human resource developmentpolicy environment of government civil servants Eastern District of Siau Island District Sitaro. (2) to analyzedifferences in the performance of employees government environments Eastern District of Siau IslandDistrict Sitaro between before and after participating in education and training (Training).This research applies descriptive and quantitative approach combined with a qualitative approach, thesample of respondents purposively set as many as 44 employees. After analyzing the data collected byapplying the product moment correlation technique and simple linear resgresi.The results of data analysis showed that (1). The average implementation of the development policy ofhuman resource quality of civil servants and the gains of government employees districts Siau Timur, bothare in the category of